1991
DOI: 10.1080/10934529109375651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organochlorine and Organotin Compounds on Active Conformation of Calmodulin

Abstract: The interaction of organotin and organochlorine compounds with calmodulin was studied in order to elucidate whether these compounds interact with calmodulin thereby affecting its active conformation. The 522 VIG ET AL.conformational changes in calmodulin were studied by using N-phenyl-1-naphthylamine (NPN) and dansyl-calmodulin as fluorescent probes. Chlordecone, an organochlorine compound, suppressed the increase in fluorescence of NPN by complex formation with calmodulin in the presence of Ca 2+ and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Chlordecone also decreased the activity of calmodulin-stimulated enzymes (Kodavanti et al, 1988(Kodavanti et al, , 1989cVig et al, 1990bVig et al, , 1991 and of enzymes integral to maintenance of neuronal energy and ionic gradients; Na+K+ATPase (Folmar, 1978;Desaiah et al, 1980a,b;Desaiah, 1981;Bansal and Desaiah, 1982;Chetty et al, 1983b;Singh et al, 1984;Jinna et al, 1989), oligomycin-sensitive mg2+ATPase (Desaiah et al, 1980a(Desaiah et al, , 1980bMishra et al, 1980;Chetty et al, 1983b;Jinna et al, 1989), and Ca2+ATPase (Mishra et al, 1980;Jinna et al, 1989;Desaiah et al, 1991) activities in brain tissues have been shown to be decreased by exposure to chlordecone both in vivo and in vitro . It is unclear whether inhibition of these enzymes is directly responsible for the effects of chlordecone on intracellular calcium or whether these changes are coincident with the changes in intracellular calcium.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlordecone also decreased the activity of calmodulin-stimulated enzymes (Kodavanti et al, 1988(Kodavanti et al, , 1989cVig et al, 1990bVig et al, , 1991 and of enzymes integral to maintenance of neuronal energy and ionic gradients; Na+K+ATPase (Folmar, 1978;Desaiah et al, 1980a,b;Desaiah, 1981;Bansal and Desaiah, 1982;Chetty et al, 1983b;Singh et al, 1984;Jinna et al, 1989), oligomycin-sensitive mg2+ATPase (Desaiah et al, 1980a(Desaiah et al, , 1980bMishra et al, 1980;Chetty et al, 1983b;Jinna et al, 1989), and Ca2+ATPase (Mishra et al, 1980;Jinna et al, 1989;Desaiah et al, 1991) activities in brain tissues have been shown to be decreased by exposure to chlordecone both in vivo and in vitro . It is unclear whether inhibition of these enzymes is directly responsible for the effects of chlordecone on intracellular calcium or whether these changes are coincident with the changes in intracellular calcium.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Experiments at the cellular level have indicated effects on calcium regulation of neuronal function (End et al, 1979(End et al, , 1981Komulainen and Bondy, 1987;Bondy and Halsall, 1988;Kodavanti et al, 1988Kodavanti et al, , 1989cBondy et al, 1989;Bondy and McKee, 1990;Vig et al, 1990bVig et al, , 1991 and several enzymes involved in maintenance of ionic gradients (Folmar, 1978;Desaiah et al, 1980aDesaiah et al, ,b, 1991Mishra et al, 1980;Desaiah, 1981;Bansal and Desaiah, 1982;Chetty et al, 1983b;Singh et al, 1984;Jinna et al, 1989). For a further description of these studies, see the discussion of &dquo;Mechanisms of Action&dquo; in the section &dquo;Toxicokinetics.&dquo; Studies in animals have also examined the peripheral nerve damage associated with chlordecone exposure and have shown that the damage is to unmyelinated axons and consists of vesiculation of the Schwann cell cytoplasm and swelling of unmyelinated axons with dissolution of microtubules and inclusion of paracrystalline material in mitochondria (Phillips and Eroschenko, 1982).…”
Section: Neurological Effectsmentioning
confidence: 99%